Limits from the FUNK experiment on the mixing strength of hidden-photon dark matter in the visible and near-ultraviolet wavelength range - Andrianavalomahefa, Arnaud; Jaeckel, Joerg (Physical review, 2020)
We present results from the FUNK experiment in the search for hidden-photon dark matter. Near the surface of a mirror, hidden photons may be converted into ordinary photons. These photons are emitted perpendicularly to the surface and have an energy equal to the mass of the dark matter hidden photon. Our experimental setup consists of a large, spherical mirror with an area of more than $14\text{ }\text{ }{m}^{2}$, which concentrates the emitted photons into its central point. Using a detector sensitive to visible and near-UV photons, we can exclude a kinetic-mixing coupling of stronger than $\ensuremath{χ}\ensuremath{≈}{10}^{\ensuremath{-}12}$ in the mass range of 2.5 to 7 eV, assuming hidden photons comprise all of the dark matter. The experimental setup and analysis used to obtain this limit are discussed in detail.